Induction of metallothionein and methallothionein mRNA in rainbow-trout liver following cadmium treatment. Issue 8 (August 1984) - Bonham, Keith; Gedamu, Lashitew
Abstract : A low-molecular-weight cadmium-binding protein was induced in the livers of rainbow trout ( Salmo gairdnerii ) following a series of intraperitoneal injections of cadmium chloride. The subsequent purification and amino acid analysis of this protein showed it to be a true metallothionein. As in higher organisms, two major forms of metallothionein appeared to be present in the liver following cadmium treatment. Following a similar induction procedure total RNA was also isolated and shown to contain high levels of metallothionein-mRNA activity when assayed in a wheat-germ cell-free translation system. This activity was present in the Poly-A + -containing fraction of the total RNA. The bulk of this mRNA activity was shown to be in the 8–10S region of a sucrose gradient.